2018
DOI: 10.1186/s12879-018-3311-6
|View full text |Cite
|
Sign up to set email alerts
|

Construction sites as an important driver of dengue transmission: implications for disease control

Abstract: BackgroundIn 2013 and 2014, Singapore experienced its worst dengue outbreak known-to-date. Mosquito breeding in construction sites stood out as a probable risk factor due to its association with major dengue clusters in both years. We, therefore, investigated the contribution of construction sites to dengue transmission in Singapore, highlighting three case studies of large construction site-associated dengue clusters recorded during 2013–16.MethodsThe study included two components; a statistical analysis of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 15 publications
(20 reference statements)
2
36
0
Order By: Relevance
“…In addition, the factors including the densely populated construction sites, the strong labor intensity, high temperature, are significantly related to the increase in the number of dengue fever cases [37]. Moreover, due to the high level of urbanization in China, construction sites are emerging one after another, along with a large population of construction workers and massive mobility [11]. Once external cases are imported, dengue fever may be prevalent on the construction sites, which leads to disease outbreaks in surrounding communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the factors including the densely populated construction sites, the strong labor intensity, high temperature, are significantly related to the increase in the number of dengue fever cases [37]. Moreover, due to the high level of urbanization in China, construction sites are emerging one after another, along with a large population of construction workers and massive mobility [11]. Once external cases are imported, dengue fever may be prevalent on the construction sites, which leads to disease outbreaks in surrounding communities.…”
Section: Discussionmentioning
confidence: 99%
“…A full-blown local dengue fever outbreak occurred in 2010 at a construction site in Shenzhen City, China, which was the first of its kind in the city's history [10]. A study published in 2018 also suggested that the overall case burden of construction site-associated clusters was significantly high through three case studies of large construction site-associated dengue clusters during 2013-2016 [11]. These all suggests that construction sites may play an important role as a driver of sustained dengue transmission, modeling the transmission routes on construction sites with large population mobility is helpful to implement effective disease control and prevention.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, due to the high level of urbanization in China, construction sites are emerging one after another, along with a large population of construction workers and massive mobility [9]. Once external cases are imported, DF may be prevalent on the construction sites.…”
Section: Discussionmentioning
confidence: 99%
“…After case importation, construction sites are more likely to have secondary cases, which may then increase the number of cases entering the community and the chance of community transmission. A study published in 2018 also suggested that the overall case burden of construction siteassociated clusters was significantly high through three case studies of large construction siteassociated dengue clusters during 2013-2016 [9].…”
Section: Introductionmentioning
confidence: 98%
“…Construction sites play an important role as a driver of sustained dengue transmission [37], since rainwater-filled land excavation holes, construction materials, and equipment (e.g., water tanks, skips, canvas sheeting) can become Aedes habitats. The Singapore Contractors Association Limited (SCAL) is therefore an important partner for NEA.…”
Section: Intra-and Intersectoral Collaborationmentioning
confidence: 99%